Import Competition from Developed and Developing Countries - Grossman, Gene M. (The Review of Economics and Statistics, 1982)
Separate demand equations for imports from less-developed countries (LDCs) and imports from developed countries (DCs) were estimated for each of eleven representative product groups. Imports were found to compete quite readily with domestically produced goods, with plausible own-price and cross-price elasticities. Whereas the quantity of each type of import was found to be quite responsive to changes in the price of US home goods, each appears to be less sensitive to the price of the alternative import. An explanation that is consistent with this observation, and that finds support from detailed industry information, is that DCs and LDCs supply goods that are at different stages in the product or technology cycle, whereas US producers compete in all submarkets. This suggests that trade creation rather than trade diversion provides the predominant inroad for LDCs into the US market. 25 references, 3 tables.